Enhancing public safety in Santiago de Surco: a strategic approach to reducing crime through body cameras and technological innovation - Morgenstern, Anna-Lena (2024)
Despite its reputation as one of Lima’s safest districts, Santiago de Surco is struggling with a growing sense of insecurity among its residents and visitors. High-profile crimes, such as drive-by robberies and assaults, have drastically increased the public anxiety, particularly in areas where resources and infrastructure are lacking. The Serenazgo and police forces, though present, struggle to fully address these issues due to limitations in personnel, technology, and geographic coverage, leaving certain neighbourhoods more vulnerable to criminal activity. To address these issues, this report proposes implementing body cameras for Serenazgo officers, focusing initially on high-crime areas. This solution would enhance accountability, improve officer transparency, and build public trust. Coupled with advanced surveillance technology and real-time monitoring, the initiative aims to reduce crime rates, increase security, and foster better relationships between law enforcement and the community. The expected social impact includes improved perceptions of safety, increased trust in authorities, and enhanced law enforcement practices. Financially, the pilot program is cost- effective, scalable, and aligned with the municipality’s budget, providing a long-term sustainable solution for Surco. If successful, this initiative can serve as a model for other districts within Lima, fostering broader community trust and security throughout the city.